The Influence of Organizational Learning, Digital Transformation Readiness, and Market Orientation on Digital Service Performance in Digital-Based MSMEs - Anton Nurcahyo; Pas Mahyu Akhirianto; Iwan Henri Kusnadi; Herman Jelatu; Julinta Paulina; Tyahya Whisnu Hendratni (Institute of Advanced Knowledge and Science, 2026)
The purpose of this study is to analyze the effect of Organizational Learning, Digital Transformation Readiness and Market Orientation on Digital Service Performance in digital-based MSMEs. The research used a quantitative method with a survey method on digital-based MSMEs that were selected using purposive sampling methodology. The data were collected through online surveys and analyzed using multiple linear regression. The results showed that Organizational Learning, Digital Transformation Readiness and Market Orientation had a good and significant effect on Digital Service Performance either partially or simultaneously. The value of the coefficient of determination indicates that the changes in the Digital Service Performance can be explained by the three independent variables in this research. Digital Service Performance is most dominated by Digital Transformation Readiness. The research result shows that the quality of digital services of digital-based MSMEs is improved by the increase in organizational learning skills, digital transformation readiness, and strong market orientation. This research extends the literature of digital transformation, strategic management, and service management, and provides practical implications for MSMEs to improve quality of digital services and company competitiveness in the digital economy era.